Origin of Bentonites and Detrital Zircons of the Paleocene Basilika Formation, Svalbard - Elling, Felix J.; Spiegel, Cornelia; Estrada, Solveig; Davis, Donald W.; Reinhardt, Lutz; Henjes-Kunst, Friedhelm; Allroggen, Niklas; Dohrmann, Reiner; Piepjohn, Karsten; Lisker, Frank (Frontiers in Earth Science, 2016)
The Paleocene was a time of transition for the Arctic, with magmatic activity of the High Arctic Large Igneous Province giving way to magmatism of the North Atlantic Large Igneous Province in connection to plate tectonic changes in the Arctic and North Atlantic. In this study we investigate the Paleocene magmatic record and sediment pathways of the Basilika Formation exposed in the Central Tertiary Basin of Svalbard. By means of geochemistry, Sm–Nd isotopic signatures and zircon U–Pb geochronology we investigate the characteristics of several bentonite layers contained in the Basilika Formation, as well as the provenance of the intercalated clastic sediments. Our data show that the volcanic ash layers of the Basilika Formation, which were diagenetically altered to bentonites, originate from alkaline continental-rift magmatism such as the last, explosive stages of the High Arctic Large Igneous Province in North Greenland and the Canadian Arctic. The volcanic ash layers were deposited on Svalbard in a flat shelf environment with dominant sediment supply from the east. Dating of detrital zircons suggests that the detritus was derived from Siberian sources, primarily from the Verkhoyansk Fold-and-Thrust Belt, which would require transport over ~3000 km across the Arctic.